Quality of surgery and surgical reporting for patients with primary gastrointestinal stromal tumours participating in the EORTC STBSG 62024 adjuvant imatinib study. (October 2019) - Hohenberger, Peter; Bonvalot, Sylvie; van Coevorden, Frits; Rutkowski, Pjotr; Stoeckle, Eberhard; Olungu, Christine; Litiere, Saskia; Wardelmann, Eva; Gronchi, Alessandro; Casali, Paolo
Abstract: Background: EORTC (European Organisation of Research and Treatment of Cancer) 62024 is a phase III randomised trial evaluating adjuvant imatinib in patients with gastrointestinal stromal tumours (GISTs) and no evidence of residual disease after surgery in 908 patients from 11 countries participated. As surgical treatment aspects (tumour rupture and incomplete resection) contribute to the risk of recurrence, the data of primary surgery were reviewed. Methods: The surgical record, local pathology report and a surgical questionnaire on details of the operation had to be completed when patients entered the study. Surgeons from 5 countries, covering 8 languages, reviewed the full set of data being available from 793 patients (87.3%). Results: A known GIST was the reason for surgery in only 58% of the cases, and 12% of the patients were treated as an emergency. The R0-resection rate was 87%. The extent of resection was local excision in 17%, segmental resection in 59%, full-organ resection in 11% and multivisceral resection in 11%, with lymphadenectomy performed in 24% of the patients. Shelling out of the tumour was performed in 9.7%, and the proportion of tumours removed in parts was higher in the endoscopy/laparoscopy group. The incidence of tumour rupture (representing M1) was 9%. The consistency between preoperative and intraoperative findings was 82%. The postoperative complication rate was 7.3%. Conclusion: The standardisation of surgery in this study was inferior. Given the review data, 18% of the patients should not have participated in the trial. Quality of surgery and improperly reported intraoperative details might influence the trial results. A detailed surgical questionnaire filled out by the surgeon is mandatory before entering the patient in an adjuvant trial in GIST. Highlights: Surgeons reviewed the primary tumor resection of patients in the EORTC 62024 study. Only 56% of the patients had been operated on under the correct diagnosis. 91% of the data on the surgery form used the letter of discharge after surgery. 18% of the patients are questionable whether they should have entered the trial. The inconsistencies might influence the study results in an adjuvant trial.